2008
DOI: 10.1002/marc.200800270
|View full text |Cite
|
Sign up to set email alerts
|

High Conductivity PEDOT Using Humidity Facilitated Vacuum Vapour Phase Polymerisation

Abstract: The synthesis of high conductivity poly(3,4‐ethylenedioxythiophene) (PEDOT) films using vacuum vapour phase polymerisation is reported. Water vapour is introduced into the chamber and results suggest that it acts as a proton scavenger during polymerisation. Process optimisation leads to PEDOT films that have high conductivity and a blue‐black appearance. Poor quality films have lower conductivity and a characteristic greenish colour. UV‐vis‐NIR spectra show that poor PEDOT films are characterised by higher abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 33 publications
4
82
0
Order By: Relevance
“…Fabretto et al reported the influence of the surfactant PEG-ran-PPG on VPP-based PEDOT films. 27 Similiarly to our results, they confirmed the presence of residual copolymer within the PEDOT film after washing by means of an X-ray photoelectron spectroscopy study.…”
Section: 폴리머 제39권 제3호 2015년supporting
confidence: 89%
See 1 more Smart Citation
“…Fabretto et al reported the influence of the surfactant PEG-ran-PPG on VPP-based PEDOT films. 27 Similiarly to our results, they confirmed the presence of residual copolymer within the PEDOT film after washing by means of an X-ray photoelectron spectroscopy study.…”
Section: 폴리머 제39권 제3호 2015년supporting
confidence: 89%
“…15,26 Meanwhile, Fabretto et al suggested the role of water during the VPP process. 27 An appropriate amount of water is necessary for proton scavenging for efficient monomer polymerization. The presence of excess water, however, degrades the quality of the VPP-based PEDOT due to the formation of FTS crystallites.…”
Section: 폴리머 제39권 제3호 2015년mentioning
confidence: 99%
“…Indeed, the mat porosity was estimated to 80 ± 5 % by simple weighting experiment, using a density of 1.6 g.cm -3 previously reported for tosylate-doped PEDOT 9 . By taking into account that the PEDOT nanofibers represent only ~20 % of the sample volume, it can be estimated that individual fibers should have conductivities around 300 S/cm, a value comparable with reported VPP-PEDOT thin films 8 . The electrochemical characterization of the mats was performed under atmosphere conditions, without any special anhydrous or anaerobic condition.…”
Section: Nanofibers Characterizationsupporting
confidence: 77%
“…Figure 3). The characteristic PEDOT spectrum can be observed, with a low absorption in the visible and an increasing absorption after 700 nm, extending in the NIR region, which has been reported as a strong bipolaron absorption, indicating high level of doping 8 . The origin of the high absorption below 500 nm, uncharacteristic of PEDOT, is still under investigation.…”
Section: Nanofibers Characterizationmentioning
confidence: 80%
“…86 Fabretto et al suggest that the water is acting as an effective proton scavenger allowing polymerization to proceed. 36 For oCVD polymerization of PEDOT using FeCl 3 as the oxidizing agent, the proposed mechanism of proton scavenging is in the formation of HCl, which is easily evaporated away from the growing polymer chain. 17 The different proton scavenging pathways may be a result of the dissimilar oxidant delivery methods in the VPP and oCVD processes.…”
Section: Reviewmentioning
confidence: 99%